2018
DOI: 10.1080/2162402x.2018.1436922
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated macrophages in human breast cancer produce new monocyte attracting and pro-angiogenic factor YKL-39 indicative for increased metastasis after neoadjuvant chemotherapy

Abstract: In breast cancer, the tumor microenvironment plays a critical role in the tumor progression and responses to therapy. Tumor-associated macrophages (TAMs) are major innate immune cells in tumor microenvironment that regulate intratumoral immunity and angiogenesis by secretion of cytokines, growth factors as well as chitinase-like proteins (CLPs), that combine properties of cytokines and growth factors. YKL-39 is a chitinase-like protein found in human and absent in rodents, and its expression in TAMs and role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 72 publications
5
77
1
2
Order By: Relevance
“…The angiogenesis assay showed that recombinant YKL-39 induced tube formation of HUVEC cells 6 times higher than that observed in the negative control group, and this induction was more than 60% of positive control. The chemotactic effect of YKL-39 on primary monocytes was approximately 2 times higher after 1 h and more than 5 times higher after 3 h compared to control, and this effect was comparable with the effect of MCP-1/CCL2 chemokines [25].…”
Section: The Role Of Clps In Angiogenesis and Chemotaxissupporting
confidence: 52%
See 4 more Smart Citations
“…The angiogenesis assay showed that recombinant YKL-39 induced tube formation of HUVEC cells 6 times higher than that observed in the negative control group, and this induction was more than 60% of positive control. The chemotactic effect of YKL-39 on primary monocytes was approximately 2 times higher after 1 h and more than 5 times higher after 3 h compared to control, and this effect was comparable with the effect of MCP-1/CCL2 chemokines [25].…”
Section: The Role Of Clps In Angiogenesis and Chemotaxissupporting
confidence: 52%
“…In our study we showed that the elevated levels of YKL-39 expression in tumors after neoadjuvant chemotherapy (NAC) were associated with increased risk of distant metastasis and poor response to NAC in patients with nonspecific invasive breast carcinoma [25]. Moreover, in the study of gene expression of M2 macrophage markers (YKL-39 and CCL18) we found that in breast cancer patients, who received anthracycline-containing NAC, the absence of clinical response was associated with the presence of M2+ macrophage phenotype (YKL-39-CCL18 + or YKL-39 + CCL18-) [38].…”
Section: Clps In Cancermentioning
confidence: 89%
See 3 more Smart Citations